2019
DOI: 10.1017/s0033291719000771
|View full text |Cite
|
Sign up to set email alerts
|

How should we understand the absence of sex differences in the genetic and environmental origins of antisocial behavior?

Abstract: Available twin-family data on sex differences in antisocial behavior (ASB) simultaneously suggest that ASB is far more prevalent in males than in females, and that its etiology (i.e. the effects of genes, environments, hormones, culture) does not differ across sex. This duality presents a conundrum: How do we make sense of mean sex differences in ASB if not via differences in genes, environments, hormones, and/or cultures? The current selective review and critique explores possible contributions to these seemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 67 publications
0
4
0
2
Order By: Relevance
“…Los resultados obtenidos, mediante un análisis multigrupo, indican que el Modelo TRD funciona adecuadamente para mujeres y varones; es decir, que las variables analizadas y sus relaciones, que se derivaron del Modelo TRD y se pusieron a prueba en este trabajo, contribuyen a anticipar y explicar la conducta antisocial observada en los grupos de varones y mujeres evaluados. Con carácter general, los factores consumo de sustancias, pares antisociales y prácticas parentales (inapropiadas) serían predictores robustos de comportamiento antisocial en la adolescencia, tanto para el caso de las chicas como de los chicos, tal como se ha documentado en estudios previos (Burt et al, 2019;Cutrín et al, 2017;Trudeau et al, 2012;Weerman & Hoeve, 2012). Este resultado sostendría la idea de que los mecanismos causales del comportamiento antisocial podrían ser esencialmente comunes a ambos sexos (Cutrín et al, 2017;Javdani et al, 2011;Slawinski et al, 2019;Trudeau et al, 2012;Weerman & Hoeve, 2012) Aunque fue mayor el peso relativo del consumo de sustancias en el comportamiento antisocial de las mujeres, en ellas esta variable se relacionó de manera más débil con el resto de los factores de riesgo.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados obtenidos, mediante un análisis multigrupo, indican que el Modelo TRD funciona adecuadamente para mujeres y varones; es decir, que las variables analizadas y sus relaciones, que se derivaron del Modelo TRD y se pusieron a prueba en este trabajo, contribuyen a anticipar y explicar la conducta antisocial observada en los grupos de varones y mujeres evaluados. Con carácter general, los factores consumo de sustancias, pares antisociales y prácticas parentales (inapropiadas) serían predictores robustos de comportamiento antisocial en la adolescencia, tanto para el caso de las chicas como de los chicos, tal como se ha documentado en estudios previos (Burt et al, 2019;Cutrín et al, 2017;Trudeau et al, 2012;Weerman & Hoeve, 2012). Este resultado sostendría la idea de que los mecanismos causales del comportamiento antisocial podrían ser esencialmente comunes a ambos sexos (Cutrín et al, 2017;Javdani et al, 2011;Slawinski et al, 2019;Trudeau et al, 2012;Weerman & Hoeve, 2012) Aunque fue mayor el peso relativo del consumo de sustancias en el comportamiento antisocial de las mujeres, en ellas esta variable se relacionó de manera más débil con el resto de los factores de riesgo.…”
Section: Discussionunclassified
“…Las diferencias observadas entre mujeres y hombres en la magnitud del comportamiento delictivo han suscitado un interés sostenido por analizar los factores que podrían explicar tales diferencias (Burt et al, 2019). No obstante, los resultados de los estudios realizados a este respecto no han sido unánimes, sino fuente de constantes controversias.…”
Section: Introductionunclassified
“…There are many from which to choose. As discussed in Burt, Slawinski, et al (2019), biological males engage in significantly more aggression and antisocial behavior than do biological females across the life span, with typical Cohen's d effect sizes ranging from .4 to .8 (Archer, 2004). This male preponderance persists across numerous human societies and across most mammalian species, including humans' nearest phylogenetic cousins, the chimpanzee, and the much more peaceful bonobo (Archer, 2004).…”
Section: How Statistical Focus Constrains Causal Inferences: Some Con...mentioning
confidence: 94%
“…This male preponderance persists across numerous human societies and across most mammalian species, including humans’ nearest phylogenetic cousins, the chimpanzee, and the much more peaceful bonobo (Archer, 2004). Despite this, variance decompositions in twin-family studies have nearly all indicated that (a) the same genetic and environmental influences underlie antisocial behavior in males and females and (b) these genetic and environmental influences are equally influential in males and females (S. A. Burt, Slawinski, et al, 2019).…”
Section: How Statistical Focus Constrains Causal Inferences: Some Con...mentioning
confidence: 99%
See 1 more Smart Citation